Outcomes of Open Reduction and K-Wire Fixation of Lateral Humeral Condyle Fractures in Children Through Modified Anterolateral Henry Approach to the Elbow (Medical Forum Monthly, 2020)
Objective: To determine the outcomes of open reduction and K-wire fixation for displaced lateral humeral condyle fracture in children through modified anterolateral Henry approach to elbow.Study Design: Prospective/observational study.Place and Duration of Study: This study was conducted at the Department of Orthopedics, Quaid-e-Azam Medical College/BV Hospital/ Civil Hospital, B/pur and NMU/Nishtar Hospital, Multan from August 2017 to Jan. 2020.Methodology: Twenty eight children of both genders with neglected humeral condyle fractures were enrolled in this study. Patients’ age range was from 3 to 12 years. Patient's demographics including age, sex and cause of fractures were recorded. All patients underwent open reduction and K-wire fixation through modified anterolateral Henryapproach to the elbow. Functional outcomes were examined at follow-up.Results: Twenty two (78.57%) were males while 5 (21.43%) were females. Falling was the commonest cause of fracture found in 15 (53.57%) patients. All the patients achieved satisfactory range of motion. 20 (71.43%) patients showed excellent, 4 (14.29%) showed good, 3 (10.71%) showed fair and 1 (3.57%) showed poor outcomes. 01 (3.57%) patient developed avascular necrosis of the fractured lateral condylar fragment, 01 (3.57%) patient had premature closure of physis and pin tract infection found in 2 (7.14%) patients.Conclusion: Open reduction and K-wire fixation through anterior (Henry) approach is safe and effective surgical modality for lateral humeral condyle fractures especially in children especially in old neglected cases.